Evaluation of Total Phenolic and Flavonoid Contents, Antioxidant, and Antibacterial Activities of Crude Extracts from Roots of Diospyros Gardneri - Phonkerd, Nutchanat (Food and Applied Bioscience Journal, 2024)
This research aimed to investigate the total phenolic and flavonoid contents, along with the antioxidant and antibacterial activities present in roots of Diospyros gardneri, utilizing various solvents with different polarities. The samples underwent maceration using n-hexane, ethyl acetate, and methanol. Subsequently, the extracts obtained were subjected to phytochemical analysis to determine the levels of flavonoids and phenolics. The antioxidant activity was assessed using the DPPH method, while the antibacterial activity was tested using the disc diffusion method. The results revealed that the crude extracts contained phenolics at concentrations of 0.31, 0.60, and 0.82 mg GAE/mL sample, respectively. Additionally, they contained flavonoids at concentrations of 0.34, 0.65, and 1.38 mg QE/mL sample, respectively. The DPPH antioxidant activity percentages of the crude extracts stood at 47.08%, 79.95%, and 75.23%, respectively. The crude extracts exhibited antibacterial activity against Bacillus cereus, Staphylococcus aureus, and Escherichia coli. Furthermore, both the crude n-hexane and ethyl acetate extracts could inhibit Vibrio harveyi. Among these, the ethyl acetate extracts demonstrated significant inhibition against S. aureus (gram-positive bacteria), with the highest observed inhibition percentage recorded at 33.17±0.02%. These findings imply that the root of D. gardneri harbors bioactive compounds potentially beneficial for disease protection. Therefore, it stands as a valuable source of antioxidants and antibacterial elements, paving the way for the development of pharmaceutical applications and health products that capitalize on D. gardneri’s properties.